Fostering Transformative Learning in a Social Pediatrics Research Summer Studentship. (May 2019) - Talarico, Susanna; Zubairi, Mohammad; Daneman, Denis; Punnett, Angela; Martimianakis, Maria Athina (Tina)
Abstract : Problem: Teaching future doctors the skills necessary to address health disparities is a challenge for medical educators. In response, the authors developed and implemented the Social Pediatrics Research Summer Studentship (SPReSS) program for medical students at the University of Toronto. Approach: The curriculum incorporated research and clinical placements into a formal seminar series. Participating students were required to complete a research project and to write a reflection describing a situation that challenged their thinking. The authors and curriculum developers applied transformative learning principles not only to facilitate critical reflection and learning in the students but also as an innovative approach to program development and evaluation. The authors conducted a thematic analysis of the reflections of 23 students participating in the program in June and July 2013, 2014, and 2015 to evaluate the SPReSS program. Outcomes: The analysis revealed students' empathic responses to marginalized patients, and these responses acted as triggers for critical reflection. Students described feeling empowered to act as advocates and wrote that these feelings were reinforced through faculty members' role modeling. According to their reflections, students found the program both challenging and rewarding, particularly the integration of the clinical and research experiences which made broader sociopolitical phenomena introduced through assigned readings and seminar discussions concrete. Next Steps: The authors are exploring models, including a fourth-year selective or multiyear longitudinal experience, to support more students. They also hope to involve more community partners and to evaluate long-term outcomes of participants.